The THE ROLE OF THE @INDOMUSIKGRAM’S ACCOUNT ON THE INSTAGRAM PLATFORM AS AN EXPRESSION MEDIA IN MUSIC - Luthfi, Zulfa Nabilah; Safrina, Rien; Dwi Arini, Sri Hermawati (Program Studi Pendidikan Musik, 2021)
Abstract : The Purpose Of this Research is to obtain detailed data about the roles and functions as well as the variation of content on the @indomusikgram account, one of the accounts on the Instagram platform. The Object Of this Research is the @indomusikgram’s account focused on its role and function as a medium of expression. The Research Methodolody used in this research is descriptive qualitative with a literature study approach. The instrument used was the researcher herself. The research was conducted for 5 months from August 2020 to the end of December 2020. The Data are collected through literature review from various document sources such as journals, books, articles, internet, and online magazines. To complement the data, direct observation is also used on the @indomusikgram account and conducting interviews with the CEO (Chief Executive Officer) of @indomusikgram’s. Data analysis was carried out by making critical notes from the interview results and making notes that were colored according to the variation of the content being researched to find out their roles and functions. Variations of content on @indomusikgram’s are collaborative content such as #collabjauh, challenge content #Tantangan12BarIMG, educational content in the form of discussions on music theory such as